2020
DOI: 10.3390/mi11110959
|View full text |Cite
|
Sign up to set email alerts
|

Study on ZrB2-Based Ceramics Reinforced with SiC Fibers or Whiskers Machined by Micro-Electrical Discharge Machining

Abstract: The effects of different reinforcement shapes on stability and repeatability of micro electrical discharge machining were experimentally investigated for ultra-high-temperature ceramics based on zirconium diboride (ZrB2) doped by SiC. Two reinforcement shapes, namely SiC short fibers and SiC whiskers were selected in accordance with their potential effects on mechanical properties and oxidation performance. Specific sets of process parameters were defined minimizing the short circuits in order to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The decomposition of the conductive ceramic composites unavoidably leads to a porous and foamy microstructure shown in [11] and correlates with analytic results of plasma chemistry [51]. During machining in oil, Si 3 N 4 -TiN decomposes on conductive carbides (TiC, SiC), and alumina-zirconia forms conductive ZrC [47] and nonconductive pyrotechnically active Al 3 C 4 [52,53]. The formed Al 3 C 4 can actively hamper processing by changing the discharge gap's electrical conditions since hydrocarbon oil exhibits better electrical conductivity (1.9-4.3 Ω-m depending on oil purity) than insulating ceramics (≤10 −4 Ω-m) [11].…”
Section: Electrical Discharge Machining Of Conductive Ceramic Compositessupporting
confidence: 66%
See 2 more Smart Citations
“…The decomposition of the conductive ceramic composites unavoidably leads to a porous and foamy microstructure shown in [11] and correlates with analytic results of plasma chemistry [51]. During machining in oil, Si 3 N 4 -TiN decomposes on conductive carbides (TiC, SiC), and alumina-zirconia forms conductive ZrC [47] and nonconductive pyrotechnically active Al 3 C 4 [52,53]. The formed Al 3 C 4 can actively hamper processing by changing the discharge gap's electrical conditions since hydrocarbon oil exhibits better electrical conductivity (1.9-4.3 Ω-m depending on oil purity) than insulating ceramics (≤10 −4 Ω-m) [11].…”
Section: Electrical Discharge Machining Of Conductive Ceramic Compositessupporting
confidence: 66%
“…Schubert et al experimentally investigated electrical discharge milling (ED milling) parameters of titanium nitride toughened silicon nitride (Si₃N₄-TiN) [45]. As Si₃N₄-TiN is decomposed at a high temperature in the discharge gap, it exhibits a particular ablation The graphical presentation of conductive ceramic composites' machinability via electrical discharge machining comparing with the maximal achievable machinability for the conductive materials, where Grigoriev, JMMP, 2020 [11], Schubert, 2016 [45], Munz, 2013 [46], Quarto, 2020 [47], Grigoriev, Tech., 2020 [48], Gavrin, 2016 [49].…”
Section: Electrical Discharge Machining Of Conductive Ceramic Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…EDM oil is adopted as dielectric by lots of reports. During the EDM process, the material at the discharge point of metal workpiece and tool melt and vaporize rapidly, and the dielectric between workpiece and tool also evaporates and decomposes rapidly [3]. Due to its especial machining mechanism, electromagnetic radiation and harmful gas emission in the EDM process are more serious than traditional machining methods [4].…”
Section: Introductionmentioning
confidence: 99%
“…The machined surface presents a recast layer with good adhesion and high hardness, due to metallurgical bonding, and contains CuO 2 , TiO 2 , and TiC phases, contributing to an increase in the surface microhardness from 258.5 to 438.7 HV, which could be beneficial for wear resistance in biomedical orthodontic applications. In accordance with potential effects on mechanical properties and oxidation performance, a study on ZrB 2 -Based Ceramics reinforced with SiC Fibers and whiskers has been performed by Quarto et al [ 3 ] By means of the pulse-type characterization, results indicated how reinforcement shapes affect the energy efficiency of the process and change the surface aspect. The microEDM milling machinability of the Si 3 N 4 –TiN ceramic composite was investigated through the discharge pulse-type discrimination algorithm evaluating the material removal rate, tool wear ratio and surface quality in [ 4 ] by Marrocco et al The analysis shows that MRR was sensitive only to normal pulses, while the occurrence of arcs and delayed pulses induced unexpected improvements in tool wear.…”
mentioning
confidence: 99%